Dynamics of delivering aptamer targeted nano-drugs into cells. Issue 4 (13th January 2021) - Liu, Yulin; Yang, Yu; Zhang, Qingrong; Lu, Denghua; Li, Siying; Li, Junfeng; Yang, Guocheng; Shan, Yuping
Abstract : Gaining precise dynamics over the cellular entry of targeted nano-drug may be the most pertinent question in achieving high efficiency nano-drug. Based on force tracing technique, the dynamics of delivering targeted nano-drug into cell was explored. Abstract : A targeted nano-drug delivery system has provided great potential and benefits to the diagnosis and therapy of cancers. Cell entry is a critical step for taking effect of the targeted nano-drug. In this report, the dynamics of delivering a single aptamer targeted polyamindoamine–camptothecin–AS1411 (PAMAM–CPT–AS1411 ) nano-drug into cells was investigated using a force tracing technique based on atomic force microscopy. The results show that the specific interaction of AS1411 and nucleolin, which is overexpressed on cancer cells, enhances the efficiency of the PAMAM–CPT–AS1411 cell entry. Moreover, the specific interaction induced receptor-mediated endocytosis prolongs the duration and decreases the speed of a single PAMAM–CPT–AS1411 cell entry, which is helpful to understand the targeted nano-drugs prolonging the therapeutic drug level. However, the required force for PAMAM–CPT–AS1411 cell entry is not changed. This report will provide a novel and potential method for achieving the precise dynamics of targeted nano-drug delivery.